An analysis of the wage gap by gender: case applied to a manufacturing company in Escobedo, Mexico (GEON Journal (Management, Organizations and Business), 2019)
This article presents a characterization of the employees of a manufacturing company located in the municipality of Escobedo in the state of Nuevo León, Mexico, with data of an uprising of 114 workers in the first quarter of the year 2019, an analysis of variance is effected (ANOVA) of the characteristics of the individuals. The results show that there is a difference between the income that women receive with respect to men, and this is largely due to the levels of schooling and positions they occupy within the company.
Keywords: Salary gap; gender; Escobedo; Mexico; Human management